2016
DOI: 10.1371/journal.pone.0145709
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, Host Specialization, and Geographic Structure of Filarial Nematodes Infecting Malagasy Bats

Abstract: We investigated filarial infection in Malagasy bats to gain insights into the diversity of these parasites and explore the factors shaping their distribution. Samples were obtained from 947 individual bats collected from 52 sites on Madagascar and representing 31 of the 44 species currently recognized on the island. Samples were screened for the presence of micro- and macro-parasites through both molecular and morphological approaches. Phylogenetic analyses showed that filarial diversity in Malagasy bats forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…We suggest that the success of parasites transmitted by vectors (hematophagous arthropods) is greater than that of those transmitted by intermediate hosts (eaten by the final host), because one or more intermediate hosts infect a single host individual, while a single vector has the potential to transmit the parasite to several final hosts by means of a mechanism of micropredation of the vector to the host (Wilson et al, 2017). Likewise this genus of nematode, Litomosoides, together with Litomosa Yorke & Maplestone, 1926, are the most well-known nematode genera that parasitize bats (Ramasindrazana et al, 2016). Based on the list presented in this study, only the genus Litomosoides is registered for Peru and based on the records presented by Santos & Gibson (2015) also only for South America.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that the success of parasites transmitted by vectors (hematophagous arthropods) is greater than that of those transmitted by intermediate hosts (eaten by the final host), because one or more intermediate hosts infect a single host individual, while a single vector has the potential to transmit the parasite to several final hosts by means of a mechanism of micropredation of the vector to the host (Wilson et al, 2017). Likewise this genus of nematode, Litomosoides, together with Litomosa Yorke & Maplestone, 1926, are the most well-known nematode genera that parasitize bats (Ramasindrazana et al, 2016). Based on the list presented in this study, only the genus Litomosoides is registered for Peru and based on the records presented by Santos & Gibson (2015) also only for South America.…”
Section: Discussionmentioning
confidence: 99%
“…However, while hundreds of nematodes have been described in bats (2), their biology, life cycles and host-parasite specificity and interactions remain largely unknown (3). Onchocercid filarial nematodes, and especially the genera Litomosa and Litomosoides, occur relatively frequently in both Old World and Nearctic and Neotropical bats of the families Hipposideridae, Miniopteridae, Molossidae, Phyllostomidae, Pteropidae, Rhinolophidae and Vespertilionidae (4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Adult Litomosa and Litomosoides generally reside within the pleural and/or peritoneal cavities of bats; however, cerebral ventricles (14) or the pulmonary artery, the right ventricle of the heart and the portal vein (9), may also be favoured sites for some adult onchocercid filariae.…”
Section: Introductionmentioning
confidence: 99%
“…Bat species diversity in the eastern mesic portions of the island is lower than in the western dry zone [21,22]. In terms of microorganisms hosted by Malagasy bats, different published studies have demonstrated the circulation of viruses, bacteria, and metazoan parasites in these nocturnal mammals [23][24][25][26]. Besides parasites of potential medical importance, bats from Madagascar also host malariarelated parasites, namely the genus Polychromophilus (Haemosporida: Plasmodiidae).…”
Section: Introductionmentioning
confidence: 99%